Kajian Teknis Kestabilan Lereng Pasca Tambang Berdasarkan Sifat Fisik dan Mekanik Tanah (Studi Kasus Kecamatan Mataraman Kabupaten Banjar Kalimantan Selatan) - Norfaeda, Rahma; Rizhan, Muhammad; kartini, Kartini (Program Studi Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2021)
Post-mining slopes have the potential for landslides caused by factors such as slope geometry, rock structure, physical and mechanical properties of rock and groundwater content. Post-mining slope monitoring must be carried out to avoid more environmental problems. This study aims to determine the stability of ex-mining slopes. The soil sample used form the Mataraman District, Banjar Regency. The analytical method of a technical study based on physical and mechanical properties of the soil with a mine slope design simulation using slide 6.0 software to determine the safety factor of ex-mining slopes from several variations of slope angles. The safety factor analysis was taken from the data of the smallest cohesion value and bulk weight to represent the strength of the slope material. Based on the analysis of the value of the physical and mechanical properties of the sample against the analysis of slope stability, it was found that the post-mining slope will be stable and safe if there are no additional factors that can reduce the stability of the slope. The mine slope still has a safety factor value of > 2 which means it is stable even though the slope angle has reached 70°.